Output Torque Improvement Analysis of Segmental Rotor Permanent Magnet Flux Switching Motor Based on Finite Element Analysis - Othman, Mohammad hakimi; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2022)
The flux switching machine (FSM) is a brushless machine that has attracted a large number of researchers in developing more potential traction motors.  In general, this machine is divided into three types but this study focuses on permanent magnet flux switching machines (PMFSM). Segmental Rotor (SegR) PMFSMs have the advantage of higher torque and power density. The purpose of this project is to optimize the output torque performance by varying several motor structure parameters and comparing the output torque of the initial and final design. The initial SegR. PMFSM has been developed from the previous project and still not in optimum performance which is considered as low output torque. This project consists of two sections: JMAG- Geometry Editor is used to design the part of the motor which are the Rotor, Stator, Permanent Magnet, and Armature coil. JMAG-Designer is used to perform the 2-D Finite Element Analysis (FEA). JMAG Designer Software Version 16.0 is used to get the motor performance and compare the performance of the initial and optimized designs. Finally, the motor's output performance in terms of cogging torque, back-EMF, flux line, flux distribution, and output torque has been presented and evaluated. The initial and final design of the 12S-10P SegR. PMFSM has been proposed, and the results obtained. Throughout this project, the final design motor produced a higher output torque than the initial design, increasing by 46% from 3.3328 Nm to 6.1859 Nm. It’s proven that varying structure parameters can enhance output torque and improve motor performance.